Moroccan Arabic Consonant Clusters Resulting From Negation as an Exception to Benhallam’s SSAA: An Optimality-Theoretic Account - Belkhadir, Radouane (International Journal of Linguistics, 2022)
This article examines the status of the consonant cluster resulting after the concatenation of the discontinuous plural morpheme ma…….∫. In disconformity with Benhallam’s Syllable structure Assignment Algorithm (henceforth SSAA) which predicts that every succession of consonants is resolved in MA by inserting schwa to break hiatus, the succession of consonants after the abovementioned morphological operation does not permit schwa epenthesis. As such, it is imperative to account for the status of the final consonants and incorporate them into the syllable structure of the language. The claim of this article is that schwa is not inserted here as the ∫ of the negative morpheme is assigned an appendix which is moraless. So, it cannot make a mora in combination with the moraless schwa. The analysis is couched within the framework of Optimality Theory (OT). More specifically, the constraints that interact to account for this seeming ad hoc are both faithfulness and markedness constraints. It is argued that some faithfuness as well as markedness constraints interacting with each other are responsible for the existence of such consonant clusters.